ANALISIS PENGARUH KOMUNIKASI KRISIS TERHADAP PERUBAHAN PRILAKU DI ERA DIGITAL 4.0 - Hafied, Hasdiyanto; Cangara, Hafied (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
The aim of this research is to determine the influence of the communication crisis on millennial life and to determine the influence of the communication crisis on human behavior in the Digital Era. A descriptive scientific approach was taken in conducting this research. The goal of a qualitative approach is to investigate, characterize, and understand a phenomenon from a central perspective. In-depth interviews with two key individuals in each business tasked with managing the crisis were used to collect primary data. key informant interviews, observation and documentation. . This analysis technique basically consists of three components, namely: data reduction, data presentation and drawing and testing conclusions. Research results Crisis communication is very important for efficient crisis management because it not only reduces or ends the crisis but also, in many cases, restores the reputation of the organization to the same level. Stephane Koch explains that social media can become an emotional network in times of crisis where facts are conveyed through emoticons, special signals for emotions. Communicating the facts is a priority for some experts, while others who rely on behavioral research note that values and emotions can be key drivers for increasing risk awareness in society and for strengthening preparedness.